The Politics of Silence: Trauma and Memory in Post-9/11 American Fiction - Dr. Muhammad Adeel Khan; Musarrat Jabeen; Rizwana Iqbal (`, 2025)
This article explores the narrative role and political implications of silence in post-9/11 fiction, focusing on how contemporary novels use silence as a response to trauma, a critique of national memory, and a form of resistance. Drawing on trauma theory and memory studies, the analysis examines how authors such as Jonathan Safran Foer (Extremely Loud & Incredibly Close) and Don DeLillo (Falling Man) deploy contrasting stylistic strategies Foer through visual fragmentation and typographical experimentation, DeLillo through minimalist prose and emotional restraint to convey the unspeakable nature of grief and psychological dissociation. Such narrative gaps reflect inner confusion of characters as well as subverts conventional modes of narrative. The article also discusses post-9/11 literature as a way of criticizing the prevailing narrative of patriotism that excludes critics and oppresses racial others, especially Muslim Americans. Novels such as The Emperors Children by Claire Messud and Home Land by Sam Lipsyte contain the conflict between a personal trauma and a national propaganda to show the omissions inherent in the national commemorations. In such writings, silence is a politically mediated element of literary craft: it refuses to close, it troubles group memory, and it gives voice to the voiceless. The article claims that, by the means of form, subtext, and structure the diversity of the attitude towards silence, post-9/11 fiction does not simply reflect the trauma but, re-imagining its possibilities of representation, re-remembers it ethically. Through it, it validates silence as a storytelling requirement and as a form of cultural opposition. Keywords: Post-9/11 Fiction, Literary Silence, Trauma Theory, Cultural Memory, Narrative Fragmentation, Jonathan Safran Foer, Don Delillo, National Mourning, Political Resistance, Marginalized Voices